PENGETAHUAN TENTANG KOSMETIKA PERAWATAN KULIT WAJAH DAN RIASAN PADA MAHASISWI JURUSAN KESEJAHTERAAN KELUARGA FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - SUKRISTIANI, DWI; Hayatunnufus, Hayatunnufus; Yuliana, Yuliana (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2014)
This study aimed to describe female colleger knowledge of Family Welfare Department for cosmetic uses. Includes facial skin care and makeup cosmetics. This type of research is descriptive quantitative. Sampling technique in this study using proportional random sampling technique were 70 female colleger of Family Welfare Department year entry 2013. Techniques of Data collection using the test in the form of multiple choice questionnaire items. Data analysis technique used is descriptive analysis formula with help of a computer program Microsoft Excel. The results showed that the knowledge of the facial skin care cosmetics is included in less category (80.00%) and knowledge of makeup cosmetics is included in less category (82.86%).Keywords: Cosmetics, Care, Facial Skin, Makeup